Assessment on bird conservation status found in rubber forest plantation by using IUCN and regional classification - Zulkifli, Syaizwan Zahmir; Abdul Kadir, Radhiah; Mohammad, Mohd Ikram (Faculty of Science and Mathematics, Universiti Pendidikan Sultan Idris (UPSI), 2018)
A wealth of studies have proposed that plantations can be enhanced into an area that is rich in biodiversity, perhaps to the extent of being an off-reserve strategy area for conservation purposes. This study was carried out to evaluate the effectiveness of rubber forest plantation in harbouring and acting as an off-reserve conservation area for birds. By conserving forest fragment areas as a way to improve the heterogeneity of a landscape within a rubber forest plantation, this paper aims to determine the conservation status of birds recorded from Bukit Kuantan rubber forest plantation which adopted forest fragment conservation. A point count observation method was implemented to record any sightings of birds within this plantation landscape. Subsequently, the identified bird species were checked with the Malaysian Wildlife Conservation Act (WCA) 2010 and IUCN Red List Data of endangered species. From the context of WCA 2010, it was found that majority of birds which accounted to 70%, were classified as totally protected, 11% were classified as protected, while remaining 19% were classified as non-protected. This work also highlights observation notes on four near-threatened bird species according to IUCN Red List Data recorded at Bukit Kuantan rubber forest plantation. Through the finding, it can be postulated that the rubber forest plantation might be suitable as an off-reserve conservation area although continuous studies is deemed necessary to determine the resiliency of the birds to continue their existence particularly in this rubber forest plantation.